Community Empowerment through the Formation of Tourism Awareness Groups (Pokdarwis) To Develop the Tourism Potential of Situ Cibuyut, Lewo Baru Village - Fujianti, Wini Siti; Ardiani, Kamila Syifa; Lestari, Amik Ayu; Ramadan, Fajar Maulana; Pramudya, Muhammad; Sapari, Deden Dimas; Ul Ajilah, Assyiva; Fauzi, Annisa Salsabila (Indonesian Journal of Community Empowerment (IJCE), 2024)
Community empowerment through the establishment of a Tourism Awareness Group (Pokdarwis) in Lewobaru Village, Garut, has become a strategic initiative in the development of local tourism, especially in the tourist attraction of Situ Cibuyut. This study aims to analyze the impact of the formation of Pokdarwis on increasing community participation and village economic development. The research method used is qualitative with a descriptive approach. The results of the study show that the active participation of the community in Pokdarwis has succeeded in increasing collective awareness of the importance of maintaining and promoting local tourism potential. In addition, the synergy between the village government, the community, and other stakeholders has also proven effective in encouraging cultural preservation and creating new sustainable economic opportunities. This finding emphasizes the importance of the role of Pokdarwis as a driving force in the development of community-based tourism that is oriented towards improving the welfare of village communities.